Uma professora pomerana e sua comunidade - Koeler, Edineia (2016)
This research is bind to the research line Culture Curriculum and Teacher Training of the Post-graduation Program in Education of the Federal University of Espírito Santo and it was developed in articulated way with Research Group (CNPq) Cultures, Partnerships and Countryside Education. The investigation was fulfilled in the community of Alto Santa Maria in the city of Santa Maria de Jetibá on the State of Espírito Santo/Brazil, where it was given the teaching socialization process of the professor Marineuza Plaster Waiandt. It was investigated the struggles of the social right for scholar education in a Pomeranian Traditional Community (Decree nº 6.040/2007). Among other aspects, it analyzes the community from the resistance concept of Freire (1996), which basically consists in do not shut up against situations of denying of rights. In relation to scholar education, the results point to the benefits of the professor self-identify as member of the Traditional Pomeranian People. When this happens it favors the educative process making possible the construction of an Education for and with the Community (BUBER 1987). Thus it discuss the process of building and maintaining of the relationships of the teacher with that social context, as what this represents for the coletive struggles in favor of education in community. Based on qualitative approach in education (LUDKE and ANDRÉ, 1986; FICHTNER et al, 2013), the narrative interview brings benefits to the research in an effort to seek with the community and the teacher the data for deepening of analysis about the main problem of realized studies: How it builds the professional relationship of the Pomeranian professor in her traditional community? In relation to the conflicts impressions, struggle for education and definition of Traditional Community, is seeks theoretical bases in Brandão (2003; 2012); for the definition of community, it counts with the contributions of Buber (1987); with Paulo Freire (1996; 1999; 2005), we discuss the concept of relation, comprehended as dialogue. Can affirm that the conquer of Pomeranian professors in community was result of the collective struggle of Pomeranian for the right to scholar education. The community promotes resistance to standardized by the State in incessant seek an education which attends the rural interests. The community exempts special attention for the initial years of schooling, highlighting the bilingual Portuguese/Pomeranian professor as a relevant factor for socializing of children to scholar environment